2014
DOI: 10.1371/journal.pone.0091024
|View full text |Cite
|
Sign up to set email alerts
|

Whole Genome Sequencing of Mycobacterium tuberculosis Reveals Slow Growth and Low Mutation Rates during Latent Infections in Humans

Abstract: Very little is known about the growth and mutation rates of Mycobacterium tuberculosis during latent infection in humans. However, studies in rhesus macaques have suggested that latent infections have mutation rates that are higher than that observed during active tuberculosis disease. Elevated mutation rates are presumed risk factors for the development of drug resistance. Therefore, the investigation of mutation rates during human latency is of high importance. We performed whole genome mutation analysis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
60
0
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(68 citation statements)
references
References 23 publications
6
60
0
2
Order By: Relevance
“…We therefore found no real evidence supporting that oxidative stress is the dominant contributing factor during latent infection in our data. A similar observation was also made by Colangeli et al (Colangeli et al, 2014).…”
Section: Mutational Patterns and Within-host Selection The Diversifyisupporting
confidence: 88%
See 1 more Smart Citation
“…We therefore found no real evidence supporting that oxidative stress is the dominant contributing factor during latent infection in our data. A similar observation was also made by Colangeli et al (Colangeli et al, 2014).…”
Section: Mutational Patterns and Within-host Selection The Diversifyisupporting
confidence: 88%
“…Furthermore, Colangeli et al (Colangeli et al, 2014) have provided contrasting evidence by showing mutation rates ten times lower during latency than active disease by examining four strains, two of them latent for more than 20 years, derived from the same index case.…”
Section: Molecular Clock Ratesmentioning
confidence: 99%
“…Furthermore, two studies by Lillebaek et al provide compelling evidence from human LTBI that bacillary replication is minimal, as restriction fragment length polymorphism and insertion sequence patterns do not change over decades of latent infection (2,25). Similarly, although the number of isolates studied was very small, Colangeli et al used whole-genome sequencing to show that the mutation rates were not elevated in cases occurring more than 20 years after a TB outbreak relative to those representing recent transmission (361).…”
Section: Latency Persistence and Dormancy: Definitionsmentioning
confidence: 99%
“…They provided evidence that the mutations that arise during latency are a result of oxidative damage, which is consistent with the exposure of the bacterium to oxidative stress during adaptation to intracellular survival within macrophages (87). In order to further characterize the mutation rate of M. tuberculosis during latency in humans, Colangeli et al used epidemiological and phylogenetic analyses of two recently acquired M. tuberculosis isolates and two cases of reactivated latent infection (20 years after initial exposure) from a multidecade outbreak in New Zealand (93). They reported that during latent infection, the mutation rate was approximately 30-fold lower than that during active disease, in contrast to the macaque study results, and they did not report any evidence to suggest that oxidative damage increases the mutation rate of M. tuberculosis during latency (87,93).…”
Section: Insights Into Mixed Infections and Within-host Genetic Divermentioning
confidence: 95%
“…Two studies, one in macaques and the other in humans, estimated the mutation rate of M. tuberculosis during latency, with conflicting results (87,93). Ford et al showed that in M. tuberculosis infections of macaques, the mutation rates of M. tuberculosis were identical during active disease, latent infection, and in vitro growth (87).…”
Section: Insights Into Mixed Infections and Within-host Genetic Divermentioning
confidence: 99%